Rest/stress intradermal lymphoscintigraphy in diagnosis of lipedema - Girolamo Tartaglione (World Journal of Nuclear Medicine, 2020)
Lipedema is a chronic and progressive disease characterized by a symmetrical and bilateral swelling of the lower extremities. In general, the feet are not involved. Lipedema is believed to affect nearly 1 in 9 adult women worldwide. Despite this relatively common disease, lipedema is often confused with primary lymphedema or obesity. In clinically advanced lipedema stages, fat continues to build up and may block the lymphatic vessels causing a secondary lymphedema (Lipo-Lymphedema). We consecutively evaluated 54 women with a clinical diagnosis of lower limbs lipedema. Two doses of 99mTc-nanocolloid were injected intradermally at the first intermetatarsal space and in the lateral malleolar area. Two static planar scans were taken at rest immediately following the intradermal injection. Subsequently, all patients were asked to perform an isotonic muscular exercise (stepping) for 2 min. Then, post exercise scans were performed to monitor the tracer pathway. Subsequently, the patient was asked to take a 30–40 min walk (prolonged exercise) and delayed scans were acquired. In early clinical stages, the lymphatic flow is usually preserved and the rest/stress intradermal lymphoscintigraphy may visualize a normal lymphatic drainage with a frequent pattern (tortuous course) of the leg lymphatic pathway. In clinically advanced stages, lymph stagnation areas were observed. Unlike obesity, lipedema fat storage is resistant to dietary regimen, bariatric surgery, and physical activity. Surgical treatment (tumescent liposuction and reductive surgery) is the most effective treatment to remove adipose tissue. Complex decongestive therapies are helpful in reducing the lymph stagnation, especially in patients with advanced lipolymphedema.